Antigone Oedipus the King - Sophocles; Kitto, Humphrey Davy Findley; Hall, Edith; Sophocles; Sophocles (Oxford Oxford University Press, 1994)
Contains three of Sophocles' most famous tragedies. Includes introduction, textual note, chronology, and explanatory notes
Antigone -- Oedipus the king -- Electra..
Keywords: Sophocles -- Translations into English; Antigone (Greek mythology) -- Drama; Oedipus (Greek mythology) -- Drama; Electra (Greek mythology) -- Drama